A particle is launched at time t = 0 from ground level with initial speed v 0 at an angle θ with respect to ground. Gravitational acceleration g is downward.
Let T ( t ) be the particle's kinetic energy as a function of time, and let V ( t ) be the particle's gravitational potential energy as a function of time, measured with respect to ground. Let t f be the time at which the particle lands.
What value of θ (in degrees) makes the following true?
∫ 0 t f V ( t ) d t ∫ 0 t f T ( t ) d t = 1
Note: 0 < θ < 9 0 ∘
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I will be happy if anyone will post the solution of this problem by solving it with python programming.
Thanks in advance
Since it's not given whether air drag is present or not, we assume that it's absent. The velocity components along the horizontal direction (assumed the x -axis) and the vertical direction (assumed the y -axis) are v x = v 0 cos θ , v y = v 0 sin θ − g t , t f = g 2 v 0 sin θ
⟹ T ( t ) = 2 1 m ( v x 2 + v y 2 )
= 2 1 m v 0 2 − m v 0 g t sin θ + 2 1 m g 2 t 2
⟹ ∫ 0 t f T ( t ) d t = g m v 0 3 sin θ ( 1 − 3 2 sin 2 θ )
The y -coordinate of the projectile is v 0 t sin θ − 2 1 g t 2
⟹ V ( t ) = m v 0 g t sin θ − 2 1 m g 2 t 2
⟹ ∫ 0 t f V ( t ) d t
= 3 g 2 m v 0 3 sin 3 θ
So, the ratio is η = 2 sin 2 θ 3 − 1
For η = 1 , sin 2 θ = 4 3
Since θ is acute, sin θ = 2 3 ⟹ θ = 6 0 ° .
Problem Loading...
Note Loading...
Set Loading...
For simplicity i am taking v 0 = v
t f is the total time of journey
0 = v sin θ t f − 2 1 g t f 2
solving the above equation leads to t f = g 2 u sin θ write the expression for kinetic energy ( T ( t ) ) T ( t ) = 2 1 m ( v x 2 + v y 2 )
T ( t ) = 2 1 m ( v 2 cos 2 θ + ( v sin θ − g t ) 2 )
Lets evaluate ∫ 0 g 2 v s i n θ T ( t ) d t = ∫ 0 g 2 v s i n θ 2 1 m v 2 cos 2 θ d t + 2 1 m ∫ 0 g 2 v s i n θ ( v 2 sin 2 θ + g 2 t 2 − 2 v sin θ g t ) d t
∫ 0 t f T ( t ) d t = g m v 3 ( sin θ + 3 4 sin 3 θ − 2 sin 3 θ )
Now,lets write the expression for potential energy ( V ( t ) ) V ( t ) = m g ( v sin θ t − 2 1 g t 2 )
Lets evaluate ∫ 0 g 2 v s i n θ V ( t ) d t = 6 g 4 m v 3 sin 3 θ
condition for a particular θ ∫ 0 g 2 v s i n θ T ( t ) d t = ∫ 0 g 2 v s i n θ V ( t ) d t
g m v 3 ( sin θ + 3 4 sin 3 θ − 2 sin 3 θ ) = 6 g 4 m v 3 sin 3 θ
solving the above equation leads to in degrees θ = 6 0